Angebotsstrukturen von stationären Pflegeleistungen in Österreich: Eine empirische Bestandsaufnahme - Müller, Romy; Theurl, Engelbert (Wirtschaft und Gesellschaft, 2014)
In this paper we study the supply of long-term care in Austria. We focus on the regional structure and on the ownership of long-term care institutions in the year 2010. Thereby we exclude long-term care provided by hospitals and within the family from our analysis. Until now disaggregated empirical information on long-term care institutions in Austria is very scanty. Our paper reduces a substantial gap in the statistics of this import sector of social services. Looking at the time period 1983-2010 in an aggregated perspective of Austria we find (i) a small decrease in the density of long-term institutions, a shift to the "care role" and a reduction of the "housing role" of these institutions and a shift in the ownership from public ownership to privat-non-profit and private-for-profit ownership. The degree of market concentration of private ownership and the role of supplier chains/networks is small. There exists evidence that this change in the ownership structure will go on in the near future. But this shift will be accompanied by a stronger role of supplier chains because suppliers acting in regional networks have a substantial advantage compared to single long-term institutions. We find quite big differences in the density of long-term care institutions and the ownership structure on the district level, but also on the level of the provinces.